Mdm2-SUMO1: is bigger better? - Melchior, Frauke; Hengst, Ludger (Nature cell biology, 2000)
Covalent modification of the oncogene product Mdm2 by the ubiquitin-related protein SUMO1 protects it from ubiquitination and enhances its E3 ligase activity towards p53 in vitro. Disappearance of SUMO-modified Mdm2, which is observed upon radiation, may thus be a prerequisite for DNA-damage-induced accumulation of p53.
Gesehen am 17.08.2023